2018
DOI: 10.3899/jrheum.170366
|View full text |Cite
|
Sign up to set email alerts
|

Flares in Patients with Rheumatoid Arthritis after Total Hip and Total Knee Arthroplasty: Rates, Characteristics, and Risk Factors

Abstract: Flares are frequent in patients with RA undergoing arthroplasty. Higher baseline disease activity significantly increases the risk. Although more patients stopping biologics flared, this did not independently predict flaring. The effect of early postsurgery flares requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 33 publications
0
36
1
2
Order By: Relevance
“…In addition, where microbiologic diagnosis for septic arthritis including PJI was available, S. aureus was the most frequently reported organism in RA patients whether they were treated with TNFi (57%) or a traditional DMARDs (43%) (20). DMARDs and biologics are known to increase infection risk and are often in use by RA patients at the time of arthroplasty (21,22), but the association of DMARDs and biologics with surgical arthroplasty infections has not been directly established through randomized controlled trials performed in patients undergoing surgery (23,24). However, in a registry database study, the risk of septic arthritis including PJI was doubled for RA patients treated with TNFi, and a meta-analysis of surgical site infection in patients exposed to TNFi also showed an elevated infection risk (OR 2.47, 95% CI 1.66, 3.68) (20,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, where microbiologic diagnosis for septic arthritis including PJI was available, S. aureus was the most frequently reported organism in RA patients whether they were treated with TNFi (57%) or a traditional DMARDs (43%) (20). DMARDs and biologics are known to increase infection risk and are often in use by RA patients at the time of arthroplasty (21,22), but the association of DMARDs and biologics with surgical arthroplasty infections has not been directly established through randomized controlled trials performed in patients undergoing surgery (23,24). However, in a registry database study, the risk of septic arthritis including PJI was doubled for RA patients treated with TNFi, and a meta-analysis of surgical site infection in patients exposed to TNFi also showed an elevated infection risk (OR 2.47, 95% CI 1.66, 3.68) (20,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, a pharmaco-epidemiologic study using a large insurance database did not find an association between infliximab use and infection after arthroplasty (23). Altered immune function in active RA increases the risk of infection, and active RA at the time of arthroplasty may contribute to increased risk of PJI infection in these patients (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Patients included in this analysis were at least 18 years old and undergoing total hip arthroplasty or total knee arthroplasty as previously described . All patients met either the ACR/European League Against Rheumatism 2010 classification criteria for RA or the ACR 1987 classification criteria for RA , and had both preoperative Disease Activity Score in 28 joints using the ESR (DAS28‐ESR) scores and complete histologic scores available.…”
Section: Methodsmentioning
confidence: 99%
“…Most relapses or flare of symptoms has been attributed to tapering off or stopping biologics [40] or poorly controlled states. While nothing has been addressed in the literature specific to physical therapy treatment causing worsening of flares while tapering off biologics, Goodman et al [41] found an increased frequency of symptomatic flares in patients with rheumatoid arthritis following total hip and total knee arthroplasty. While inflammatory autoimmune disorders should not preclude dry needling, proper screening of the stability of the disease and medication status is merited to avoid overly aggressive dry-needling dosage and technique in unstable or active flares to prevent exacerbating symptoms.…”
Section: Inflammatory Autoimmune Disordersmentioning
confidence: 99%